Presence of immune factors in freshwater mussel (Hyriopsis cumingii) entails autologous serum an essential component in the culture of mantle cells - Bai, Zhiyi; Wang, He; Li, Xuenan; Shen, Xiaoya; Chen, Yige; Fu, Yuanshuai; Li, Wenjuan (Frontiers in Immunology, 2023)
Mussel cell culture is a challenging problem and serum serves a crucial biological role in cell culture as an autologous supply and an immunizing agent. In this study, the biology (calcium ions, total protein, pH, and osmotic pressure) of fetal bovine serum (FBS) and Hyriopsis cumingii serum (HCS) was investigated, and the development of Hyriopsis cumingii (H. cumingii) mantle cells in HCS and FBS systems was examined. The results showed that total protein, calcium ions, and osmotic pressure varied significantly (p<0.05). The activity of mantle cells was superior in the HCS culture system to that in the FBS culture system. The label-free technique was used to distinguish the two serum proteins to investigate the supportive effect of autologous serum on cell culture. These were examined for 109 unique proteins and 35 particular HCS proteins. Most differentially expressed proteins (DEPs) were involved in immune response, cell differentiation, and calcium ion binding. Furthermore, immune factors such as HSP, CALR, APOB, C3 were identified with significant differences. HSP was significantly more present in HCS than in FBS as an endogenous protective protein that regulates immune system function, cell differentiation, transport, and activity regulation. Parallel reaction monitoring (PRM) analysis was carried out to validate the expression levels of 19 DEPs, indicating high reliability of the proteomic results. This study reveals the important role of immune factors in mussel cell culture, providing a theoretical basis for explaining the applicability of autologous serum in cell culture. It is also helpful in improving the cell culture conditions of mussels.